Th17-cells in depression: Implication in multiple sclerosis - Melnikov, Mikhail; Lopatina, Anna (Frontiers in Immunology, 2022)
Depression is one of the most common neuropsychological symptoms of multiple sclerosis. However, in addition to mood disorder, depression can also influence on multiple sclerosis course. The mechanism of this dependence is not fully understood. The recent studies suggest the possible common immune mechanisms in the pathogenesis of depression and multiple sclerosis. In particular, it was shown that along with biogenic amines disturbance, neuroinflammation also play an important role in the pathogenesis of depression. Significant attention is drawn to Th17-cells subsets, which are considered as critical players in the pathogenesis of inflammatory diseases of the central nervous system, including multiple sclerosis. This brief report reviews the literature data on the role of neuroinflammation in the reciprocal influence of multiple sclerosis and depression with focus on Th17-cells, which may underlie pathogenetic mechanisms of both this diseases.